SOCIALIZATION – WAY OF PREVENTING OR GENERATING DEVIANT BEHAVIOR - GAVRIȘ, Aurora-Elena (International Journal of Legal and Social Order, 2022)
The human being is born, lives and develops, generally, in a social setting, more or less favorable and sometimes even hostile; the individual forms of a social personality following the socialization process goes through, a social personality that will be the expression of a status, he will hold and a role he will exercise; of course, there is the possibility that the person will manifest behavioral deviance or even delinquency throughout along his life; also, most often, the person can be a respectable person all his life, through attitude, behavior and conformity to moral and social norms; we thus outline, at a theoretical level, a human behavior according to social norms, that is, which will comply with the promoted and desired social order, and another, which will violate the norms and prescriptions, will deviate from them, producing social disturbances through the manifested deviance. The classic concept of socialization of the person unfolds in its temporal stages and in the appropriate social environments institutionally, but also through modern means, offered by the media and the presence of the Internet with the virtual space that offers numerous possibilities for communication and exposure of life experiences.